Representing Africa : colonial anthropology revisited - Burton, John W.
This article was got from the journal of Asian and African studies, vol. xxvii, no. 3-4 (1992)
AR/SIC/1/2/21
English
Shelf no. 2
Keywords: Anthropology -- Africa